Examination of The Relationship Between Exercise Addiction and Physical Self-Concept Levels of Students Studying at The Faculty of Sport Sciences - Hacı Ahmet Pekel; Ebru Olcay Karabulut; Mehmet Ali Üzgü (Selcuk University, 2023)
The aim of this study is to examine the relationship between exercise addiction and physical self-esteem levels of students studying at the Faculty of Sport Sciences. Survey method was used as the research design in the study. The scope group of the study consisted of students studying in the faculties of sport sciences of 7 universities, randomly selected as one from each geographical region of Turkey. "Personal Information Form" was used to obtain the socio-demographic information of the participants, "Exercise Addiction Scale (EIS)" was used to determine the level of exercise addiction and "Physical Self Scale" was used to determine the level of physical self. Normality test was performed on the data obtained and it was determined that the data were normally distributed. Independent Sample T test was used for pairwise comparisons, One Vay ANOVA for multiple comparisons and Tukey HSD test was used to determine the source of difference. Pearson correlation test was used to determine the relationship between the two scales. In the statistical analysis and interpretations of the data, p<0.05 significance level was taken into consideration. As a result; gender, age, department of study, class of study, perceived economic level, sport branch and perception of exercise addiction affect the level of exercise addiction. In addition to this, gender, age, department of study, class of study, perceived economic level, sport branch and perception of exercise addiction affect the level of physical self. Finally, it was concluded that there was a positive correlation between exercise addiction and physical self-image level. According to these results; in order to facilitate students' access to psychological counselling services within educational institutions and to prevent false body perception that may occur due to the influence of the media, it may be recommended to conduct informative studies on healthy and realistic body standards in schools.